Systems Biology of Yersinia pestis - V. L. Motin (Проблемы особо опасных инфекций, 2013)
Omics technologies developed in recent years significantly changed our approach in study molecular biology of bacterial pathogens. The research now can be conducted at a whole-genome level enabling us to simultaneously measure variable components, such as proteins, nucleic acids, metabolites, cell lipid composition, etc . This complex work requires a constant interaction of multi-disciplinary experts to integrate biology, instrumentation and computational science. A multi-omics research (transcriptomics, proteomics, metabolomics) was applied to Y. pestis -centric system biology study. Integrated omics datasets allowed to refine genome annotations, discover novel putative virulence factors, build regulatory networks, and create an interactive computational metabolic model.